Impacto del acoso callejero en estudiantes universitarias de tercero y quinto ciclo de la EAP de trabajo social- UNT, 2017. - Calderón Infantes, Nayda Lili (2018)
Street harassment is a type of gender violence, considered nowadays as an act where power is exercised over another person because he is more vulnerable. Currently in our society street harassment is part of the interpersonal violence that is exercised in this case to women and is socially accepted. The university population of the professional academic school of social work mostly consists of females so it was possible to identify the problem. This research report has the title "IMPACT OF STREET HARASSMENT IN THIRD AND FIFTH STUDENTS OF THE SOCIAL WORK EAP-UNT EULAR CYCLE, 2017", which shows the results that identify how street harassment impacts on students education increases vulnerability and gender discrimination. this report describes the characteristics of the harassment suffered, the harasser's gender, the forms of harassment suffered, frequent spaces where harassment occurs, the change in habits that the victim generates in the harassment, reactions of both the victim and the aggressor, based on to the personal experiences of university students. This research report is based on the theoretical approaches of gender, human development, human rights that have guided the analysis of research, likewise with regard to the methodology have been used Inductive-deductive, descriptive, statistical, what a They had their instruments for the necessary data collection, which is why the population involved was a total of 90 students of EAP - Social Work - UNT- 2017. The results of this investigation evidence and describe in detail the problem posed.